2008
DOI: 10.1111/j.1600-0765.2008.01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone healing in critical‐size defects treated with platelet‐rich plasma activated by two different methods. A histologic and histometric study in rat calvaria

Abstract: It can be concluded that the type of activator used to initiate PRP clot formation influences its biological effect on bone healing in CSD in rat calvaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 33 publications
1
53
0
8
Order By: Relevance
“…5). For the sham operation, these results were very similar to the results reported by Messora et al 20) . Fukushima et al 7) reported that DNA/protamine complex paste gradually degraded after implantation into the soft tissue of rats, and deep purple complex fragments were observed 3 days after implantation, and had completely disappeared from the tissues within 10 days after implantation.…”
Section: Histological Evaluationsupporting
confidence: 82%
See 2 more Smart Citations
“…5). For the sham operation, these results were very similar to the results reported by Messora et al 20) . Fukushima et al 7) reported that DNA/protamine complex paste gradually degraded after implantation into the soft tissue of rats, and deep purple complex fragments were observed 3 days after implantation, and had completely disappeared from the tissues within 10 days after implantation.…”
Section: Histological Evaluationsupporting
confidence: 82%
“…4, treatment with DNA/protamine complex paste showed a significantly higher bone regeneration areas than the sham operation. Messora et al 20) reported that newly formed bone areas in a calvarial defect of 8 mm were approximately 6 % and 12% one month and 3 months after the sham operation, respectively. Their results were very similar to the results obtained from the present study.…”
Section: Histological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several aspects were considered to guarantee their integrity in the PRP samples, such as the choice of the anticoagulant, the speed of the centrifugation, the activator used to initiate PRP clot formation, and the amount of time between activation of the PRP and its clinical use. 24,[30][31][32] According to Marx, 3 platelets damaged or rendered nonviable by PRP processing will not secrete bioactive GFs, and may result in disappointing outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The quantity and quality of bone that forms in an osseous defect is influenced by the type and age of the animal, the stability and size of the defect, and other factors 36) . In the present study, a calvarial defect of 8 mm in diameter was created for the animal examination because it had been previously demonstrated to be a critical size for rat calvarial bone defects 37,38) . Bone formation in the calvarial defect model occurs under unloaded conditions.…”
Section: Discussionmentioning
confidence: 99%